Role of Vitamin B12 and folate in metabolic syndrome - Current trends and future perspectives - Kowshik Chandramahanti; Akhila Chiratanagandla; Swarnadeep Ammula; Bhargav Krishna Kommineni (Wolters Kluwer Medknow Publications, 2023)
The metabolic syndrome (MS) refers to a collection of illnesses which together alleviate the potential risk of insulin resistance, atherosclerotic cardiovascular disease, diabetes mellitus, and vascular and neurological outcomes such as the cerebrovascular accident. Vitamin B12 is one of the major water-soluble vitamins found among the animal products such as the dairy products, eggs, and red meat. Folate is an essential nutrient which is naturally present among the foods in a stable reduced form and is present in an oxidized form (folic acid) among the fortified foods and dietary supplements. Homocysteine and methylmalonic acid levels in the blood are raised when Vitamin B12 is deficient, both of them can serve as indicators of deficiency of Vitamin B12 biochemical. Excess folate, primarily from the increased intake of folic acid, can interfere with the metabolism of cobalamin and exacerbates the Vitamin B12 deficiency symptoms, according to previous studies. Furthermore, the influence of supplementing Vitamin B12 and folate remains a largely uncharted field, hence, a lot more observational studies and randomized controlled trials are required to determine how vitamin supplementation affects each and every component of MS.